Studi Pengaruh Jenis Kemasan dan Ketebalan Plastik Terhadap Karakteristik Mutu Rebung Bambu Tabah (Gigantochloa nigrociliata Kurz) Kering - Lobo, Yustina Angreny; Kencana, Pande Ketut Diah; Arda, Gede (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 2 No 1 (2014): Maret, 2017)
This study was conducted to determine the effect of the type of plastic packaging with different thickness of the characteristics of dried bamboo shoots (Gigantochloa nigociliata KURZ). This study is also expected to increase the shelf life of bamboo shoots by using proper plastic packaging. The design used was a randomized block design with two factors. The first factor is the type of plastic with two different thicknesses with details P1: dried bamboo shoots packed with a thickness of 0.04 mm Polypropylene plastic, P2: dried bamboo shoots packed with a thickness of 0.08 mm PP plastic, P3: dried bamboo shoots packed with PE plastic thickness 0.04 mm, P4: bamboo shoots packed with a thickness of 0.08 mm Polyethylene plastic. And the second factor is the storage time with details of H1: 10 days, H2: 20 days, H3: 30 days, H4: 40 days. The study was repeated three times. Parameters observed in this study include analysis of weight, water content, texture and water absorption. The results of this study indicated that the type of plastic packaging, thickness and storage time gave significant effect on characteristics of dried bamboo shoots. The polypropylene plastic with a thickness of 0,08 mm is the best type of plastic packaging, because it has the lowest water content and lowest weight during 40 days of storage